Memories Of The Creativity: A Visual Criticism Of The Evolution Of Creativity In The Era Of Artificial Intelligence: Memories Of The Creativity: A Visual Criticism Of The Evolution Of Creativity In The Era Of Artificial Intelligence - Ahmad Naswin; I Putu Adi Saskara; I Putu Adi Pratama (Warna Komunikasi, 2025)
Alit Kumala Dewi's "Memories of the Creativity" poster is a powerful visual response to the shifting meaning of creativity in the posthuman era, where artificial intelligence (AI) technology is beginning to redefine creative processes that were previously closely tied to human experience. By combining the image of an old man with closed eyes, a collage of manual art activities, and the symbolism of AI invasion in a contrasting visual composition, the poster highlights the existential tension between the memory of traditional creativity and the new, increasingly digitalized reality. This work is not only an aesthetic statement, but also a philosophical reflection on the changing role of humans in artistic creation. This article analyzes the poster using a theoretical approach based on the concepts of posthumanity, simulacra, creative nostalgia, and a critique of cultural automation. Through an in-depth reading, it is revealed how the poster functions as a social critique and a contemplative invitation to the position of humans in the creative landscape of the future.